2006
DOI: 10.1016/j.ejheart.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, contemporary management and one‐year mortality in patients with severe acute heart failure syndromes: The EFICA study☆

Abstract: Background: Little is known about the epidemiology of acute decompensated heart failure (ADHF) in patients admitted to intensive and coronary care units (ICU/CCU). Observational data may improve disease management and guide the design of clinical trials. Aims: EFICA is an observational study of the clinical profile, management and survival of ADHF patients admitted to ICU/CCU. Methods: The study included 599 patients admitted to 60 ICU/CCUs across France. Relevant data was recorded during hospitalisation. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
247
5
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(283 citation statements)
references
References 36 publications
19
247
5
12
Order By: Relevance
“…The length of hospital stay of our patients was comparable to that found in other European registries [29][30][31][32]. Our patients who developed WRF had a longer duration of hospital stay and this may be important both with respect to quality of life and the cost of treatment.…”
Section: Clinical and Prognostic Value Of Wrfsupporting
confidence: 82%
“…The length of hospital stay of our patients was comparable to that found in other European registries [29][30][31][32]. Our patients who developed WRF had a longer duration of hospital stay and this may be important both with respect to quality of life and the cost of treatment.…”
Section: Clinical and Prognostic Value Of Wrfsupporting
confidence: 82%
“…Also of importance is the fact that identification of CAD patients was based not only on clinical grounds, but also on coronary angiography data available in 69% of them, but also in 43% of those with non‐CAD. This is in contrast to most existing series of APE7, 10, 23 or acute heart failure,1, 2, 3, 4, 5, 13 where angiographic data are not provided. Of interest is the documentation of significant coronary artery stenosis in 32% of non‐CAD patients who underwent cardiac catheterization, pointing to the concomitant presence of CAD in patients with the primary diagnosis of valvular heart disease.…”
Section: Discussionmentioning
confidence: 90%
“…Most series that have analyzed total mortality in patients with acute heart failure have reported only a 1‐year follow‐up with mortality rates ranging from 17.4% to 34%5, 11, 12, 13, 14 and higher in patients admitted to a critical care area (46.5%) 4. Predictors of 1‐year mortality appeared also to be age,12, 13, 14, 15 admission blood pressure,13, 15 anemia,13 renal failure,12, 13, 15 left ventricular dysfunction, and acute coronary syndromes 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, however, have shown that up to 30%-50% of patients admitted with acute HF may have preserved LVEF [14,15,[18][19][20][21]. Patients with preserved LVEF have a high rate of rehospitalisation and a similar, or only slightly lower, mortality, compared to patients with low LVEF [14,15].…”
Section: Systolic Versus Diastolic Left Ventricular Dysfunctionmentioning
confidence: 99%